2020
DOI: 10.1007/s00330-020-06915-5
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of CT signs of 2019 novel coronavirus (COVID-19) pneumonia

Abstract: Objectives To characterize and interpret the CT imaging signs of the 2019 novel coronavirus (COVID-19) pneumonia in China. Materials and methods The CT images of 130 patients diagnosed as COVID-19 pneumonia from several hospitals in China were collected and their imaging features were analyzed and interpreted in detail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
129
1
10

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(150 citation statements)
references
References 18 publications
(20 reference statements)
6
129
1
10
Order By: Relevance
“…The present study showed that the predominant pulmonary parenchymal pattern for this disease is ground-glass haze/opacity followed by consolidation, as seen in 88.5 and 52.8% of patients respectively. This is comparable to the other studies in the Chinese population [15][16][17][18][19]. A study by Chung et al showed that ground-glass opacification was the most frequently encountered imaging feature, as observed in 86% of the study population.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The present study showed that the predominant pulmonary parenchymal pattern for this disease is ground-glass haze/opacity followed by consolidation, as seen in 88.5 and 52.8% of patients respectively. This is comparable to the other studies in the Chinese population [15][16][17][18][19]. A study by Chung et al showed that ground-glass opacification was the most frequently encountered imaging feature, as observed in 86% of the study population.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, according to that study, patients with moderate disease exhibited reversed halo sign more than those with severe disease (31.3 vs 13% respectively) [18]. Another study by Jing et al showed a reversed halo sign in 4.6% of the patients [17]. The findings of our study contrast with these results as they showed no reversed halo sign in any of the patients.…”
Section: Discussioncontrasting
confidence: 84%
“…The methodological quality assessment is displayed in Table 2. Risk of bias with respect to method of patient selection was rated "unclear" in 13 studies, 14,[20][21][22][23]27,28,[32][33][34]36,38,41 because these studies did not report whether patients were randomly or consecutively included. Risk of bias with respect to patient spectrum was rated "high" in eight…”
Section: Methodologic Quality Assessmentmentioning
confidence: 99%
“…Indeed, it is not clear if COVID-19 will leave permanent lung and/or physical damage and, if so, to what extent. Alterations of lung tissue such as ground-glass opacities, consolidation, vascular thickening, bronchiectasis, pleural effusion, crazy paving pattern and irregular solid nodules [2], may progress in over 80% of patients [3]. Persisting limitations in respiratory function and gas exchange will likely be more pronounced in the subgroup of ICU survivors.…”
mentioning
confidence: 99%